INTERVENCIÓN DEL ESTADO EN EL SECTOR FINANCIERO (2016)
The financial system in Colombia as any country in the world is formed by different institutions, authorities and economic agents operating in the market for professional and specialized way, generating wealth and development economies. Due to the large resources mobilized through such entities and the sector’s importance in the economy of a country, state intervention in the financial sector is necessary.The major financial crises that have occurred throughout history teach us that the financial markets by themselves do not always work properly, as they present faults like any other market, and it is for these failure that state presence is justified, using tools such as regulation and supervision, thus allowing markets behave properly generating efficiency but also equity.